Preclinical research models for endometrial cancer: development and selection of animal models - Xue, Yang; Shi, Wei; Lun, Bing; Kan, Meilin; Jia, Mengling; Wu, Yuelin; Yang, Li (Frontiers in Oncology, 2025)
Endometrial cancer (EC) is the most common gynecological malignancy in developed countries, with rising incidence in recent years. Experimental animal models are crucial for studying the pathogenesis, advancing diagnostic methods, and developing new treatments. We review five main EC animal models. The use of spontaneous and chemically-induced models has decreased, with transgenic mouse and xenograft models becoming the most widely used. These models better simulate tumor molecular mechanisms and treatments, with the organoid-based patient-derived xenograft model (O-PDX) showing great promise in drug screening and personalized therapy. The application of humanized models remains limited due to technical challenges and high costs. In this review, we highlight the strengths and limitations of each model to guide researchers in their selection.